Chemical Profile and Multicomponent Quantitative Analysis for the Quality Evaluation of Toad Venom from Different Origins - Cao, Yueting (Molecules, 2019)
Toad venom (Chansu), a traditional Chinese medicine (TCM), has been widely used for treating various cancer. However, it is considerably difficult to evaluate the quality of Chansu due to its complex chemical compositions. Hence, finding the characteristic ingredients and developing a scientific and comprehensive quality evaluation method are essential for guaranteeing the safety and efficacy of Chansu. In this paper, the chemical composition database of Chansu was successfully established and HPLC-ESI-Q-TOF-MS/MS was applied for chemical profiling of the ingredients in Chansu. In total, 157 compounds were identified, including 22 amino acids, 8 alkaloids, 54 bufogenins, 63 bufotoxins, and 10 other compounds. Furthermore, HPLC fingerprints and quantitative analysis of its multicomponent were successfully developed to evaluate the quality consistency of Chansu from different origins. The results suggested that the HPLC fingerprint of Chansu could be divided into an amino acid and alkaloid region, as well as a bufogenins and bufotoxins region. The fingerprint profile of Chansu from different geographical origins were different, indicating that its quality was affected by the geographical factors. In addition, seven characteristic peaks were selected as the quantitative markers to evaluate the quality of the Chansu. The Kruskal–Wallis test illustrated that the contents of seven bufogenins in Chansu were significantly (p < 0.01) different among different origins. The total contents of the seven compounds ranged from 100.40 to 169.22 mg/g in 20 batches of Chansu samples. This study demonstrated that integrating HPLC-ESI-Q-TOF-MS/MS, HPLC fingerprints, and multicomponent quantitative analysis coupled with chemometrics was a comprehensive and reliable strategy for evaluation of Chansu in both qualitative and quantitative aspects. In addition, our study represented the most comprehensive characterization on the chemical compositions of Chansu, which could provide important reference information for the discovery of potential bioactive compounds.